小児の上顎洞内に進展した大きな複雑性歯牙腫の1例 - 足立, 健; 町田, 好聡; 渋谷, 亜佑美; 越沼, 伸也; 山本, 学; 堀澤, 建介 (日本口腔外科学会雑誌, 2017)
Complex odontoma is classified as odontogenic epithelium with odontogenic ectomesenchyme with or without hard tissue formation according to the WHO histological classification of odontogenic tumors (2005). It rarely occurs in the maxillary sinus.　We describe an extremely rare huge complex odontoma extending to the right maxillary sinus of a child.　A 12-year-old girl was referred to our department for further evaluation of the right maxillary sinus. Panoramic radiography revealed a radiopaque mass in the right maxillary sinus. A computed tomographic scan showed a high density mass in the maxillary sinus. The lesion was enucleated with the patient under general anesthesia. The lesion resected from the maxillary sinus measured 50 × 35 × 30 mm and was light gray and bony hard. The definitive histopathological diagnosis was a complex odontoma.　As of 4 years and 3 months after the operation, the patient showed no signs of recurrence.